The Native units of the concept of “humanity” in the book of Bishop Ukhtanes “History of Armenia” - Dilbaryan, Narine (Bulletin of Yerevan University B: Philology, 2024)
The Native units of the concept of “humanity” in the book of Bishop Ukhtanes “History of Armenia”. - In the book of Bishop Ukhtanes “History of Armenia” almost all the key words of the ancient Armenian language of the concept of humanity are attested, etymological and semantic studies of which prove that all the primary units denoting the concept of humanity were of Indo-European origin. Their diachronic analysis proves that they are used at all stages of the literary Armenian language, as well as in dialects. They are inherited from the proto-language and have a thousand-year history. The Ancient Armenians, who emerged from the Indo-European unity, already had a highly developed social life with its clear hierarchy, various relationships, family, friendly and professional subsystems, the names of which are Indo-European, borrowings here are few and occasional. The words of the concept of humanity have undergone few changes, they represent stable units, some of them have become archaisms. At the same time, we also have cases of expansion of meaning; many words of a given concept have become forms of address. Some units acquired obvious terminological meaning, enriching the vocabulary of the Modern Armenian language.